2017
DOI: 10.1016/j.bcp.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, properties, and inhibitor sensitivity of zebrafish catechol-O-methyl transferases (COMT)

Abstract: BCA-bicinchoninic acid (71068) BCIP-5-bromo-4-chloro-3-indolylpho sphate (65409) CHRM1-cholinergic receptor muscarinic 1 DHBAC-dihydroxybenzylacetic acid (72) DIG-digoxigenin (15478) DOPAC-dihydroxyphenylacetic acid (547) L-DOPA-3,4-dihydroxy-L-phenylalanine (6047) GAD67-glutamic acid decarboxylase (brain, 67 kDa) GFAP-glial fibrillary acidic protein GluN2A-glutamate ionotropic receptor NMDA type subunit 2 A GST-glutathione-S-transferase 5-HIAA-5-hydroxindoleacetic acid (1826) 3-MT-3-methoxytyramine (1669) NBT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Quercetin 3-O-glucuronide is one of the most common quercetin metabolites produced by phase II biotransformation in small intestine and liver cells, besides sulfated and methylated derivatives [27]. Once in the kidney, the entry of quercetin metabolites in tubular cells takes place mainly through influx transporters in the basolateral membrane and transporters in the apical membrane via tubular reabsorption [28]. It has been reported that glucuronide conjugates, such as quercetin 3'-O-glucuronide, have a high affinity for OAT3, whereas quercetin 3-O-glucuronide and quercetin 7-O-glucuronide are weak substrates of OAT1 and OAT3 [29].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin 3-O-glucuronide is one of the most common quercetin metabolites produced by phase II biotransformation in small intestine and liver cells, besides sulfated and methylated derivatives [27]. Once in the kidney, the entry of quercetin metabolites in tubular cells takes place mainly through influx transporters in the basolateral membrane and transporters in the apical membrane via tubular reabsorption [28]. It has been reported that glucuronide conjugates, such as quercetin 3'-O-glucuronide, have a high affinity for OAT3, whereas quercetin 3-O-glucuronide and quercetin 7-O-glucuronide are weak substrates of OAT1 and OAT3 [29].…”
Section: Discussionmentioning
confidence: 99%
“…Renal cells also show COMT activity [41]. These enzymes carry out efficient methylation of quercetin aglycones to form methylated derivatives in kidney cells.…”
Section: Quercetin Metabolism In Tubular Cellsmentioning
confidence: 99%
“…The role of COMT in metabolizing dopamine in zebrafish is not well understood, but suggested that the presence of 3MT, the product of dopamine methylation, is evidence of the role of COMT in metabolizing dopamine. Another study showed that comta mRNA expression was abundant in the gut, gills, and spleen, while comtb mRNA expression was abundant in the liver and brain, highlighting that comtb is more relevant to central nervous system than comta [9]. Although COMT inhibition did not result in an increased level of dopamine in larval zebrafish, an increase in DOPAC was observed, indicating activation of oxidative metabolism [9].…”
Section: Dopamine Signaling In Zebrafishmentioning
confidence: 99%
“…Another study showed that comta mRNA expression was abundant in the gut, gills, and spleen, while comtb mRNA expression was abundant in the liver and brain, highlighting that comtb is more relevant to central nervous system than comta [9]. Although COMT inhibition did not result in an increased level of dopamine in larval zebrafish, an increase in DOPAC was observed, indicating activation of oxidative metabolism [9]. D2 autoreceptor plays a role in inhibiting neurotransmission by a negative feedback mechanism.…”
Section: Dopamine Signaling In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation